Aggregation‐Induced and Polymorphism‐Dependent Thermally Activated Delayed Fluorescence (TADF) Characteristics of an Oligothiophene: Applications in Time‐Dependent Live Cell Multicolour Imaging. Issue 24 (24th October 2019) - Sarkar, Samir Kumar; Pegu, Meenakshi; Behera, Santosh Kumar; Narra, Siva Krishna; Thilagar, Pakkirisamy
Abstract: Typically, molecules with a twisted donor–acceptor (D‐A) architecture have been exploited for constructing thermally activated delayed fluorescence (TADF) materials. Herein, we report the first example of a thiophene‐based thermally activated delayed fluorescent molecule without a D‐A architecture. Compound 1 (2, 5‐bis(2, 2‐di(thiophen‐2‐yl)vinyl)thiophene) is conformationally flexible and shows weak fluorescence in the solution state but displays bright TADFin both condensed and solid states. Compound 1 crystallized in two different polymorphs (1 a and 1 b ). Interestingly, both polymorphs show distinctly different TADF features. The broad spectral features and the TADF characteristics of 1 have been explored for the time‐dependent multicolor (green, yellow and red) imaging of living cells. Abstract : Intriguing polymorphism‐dependent thermally activated delayed fluorescence (TADF) properties of an oligothiophene are reported. The broad emissive TADF characteristics are used for time‐resolved multicolor (green, yellow and red) live cell imaging.